2014
DOI: 10.5742/mewfm.2014.92543
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Stibogluconate Treatment for Cutaneous Leishmaniasis : A Clinical Study of 43 Cases from the North of Jordan

Abstract: Objective: to study the efficacy of Sodium Stibogluconate intramuscular injections in the treatment of cutaneous leishmaniasis, safety and side effects. Method: A total 43 patients were seen over a period of 12 months, from January 2009 to December 2010. All cases were seen at Prince Rashed Military Hospital in the north of Jordan. The diagnosis of localized cutaneous leishmania was made on clinical grounds proved by leishmania smear or skin biopsy. The distribution of patients according to gender, age groups,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
1
1
0
Order By: Relevance
“…The distribution of cutaneous leishmaniasis in rural area was higher than the urban area, this result is agreement with other Iraqi studies as (Rahi et al, 2013) and (Al-Samarai et al, 2016), in Libya (Sabra et al, 2013, in Syria (Al-Nahhas and Kaldas 2013), in Jordan (Al-Athamneh et al, 2014), in Iran (Mehdi et al, 2016), and in Turkey (Fahriye et al, 2017). However, a different result had been recorded by (AL-Hucheimi 2014; Al-Atabi 2014).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The distribution of cutaneous leishmaniasis in rural area was higher than the urban area, this result is agreement with other Iraqi studies as (Rahi et al, 2013) and (Al-Samarai et al, 2016), in Libya (Sabra et al, 2013, in Syria (Al-Nahhas and Kaldas 2013), in Jordan (Al-Athamneh et al, 2014), in Iran (Mehdi et al, 2016), and in Turkey (Fahriye et al, 2017). However, a different result had been recorded by (AL-Hucheimi 2014; Al-Atabi 2014).…”
Section: Discussionsupporting
confidence: 89%
“…In Saudi Arabia (Amin et al, 2013) documented that the incidence rate of CL was higher in males than in females from 2000 to 2010. In Syria (Shanehsaz and Ishkhanian 2013) found that Syrian males are more infected with the parasite than females, In Jordan (Al-Athamneh et al, 2014), The same result in Turkey , This is probably happened due to the cultural habits of most areas.…”
Section: Discussionmentioning
confidence: 86%